How to set-up an effective Sacral Neuromodulation service - Franco Marinello, MD,PhD. (Continence)
Over the last 30 years, Sacral Neuromodulation (SNM) has become the first-line surgical treatment in patients with fecal and urgency urinary incontinence with over 400,000 patients implanted worldwide. Its favorable long-term functional results and the minimal invasiveness of the technique has broadened potential new indications. Also, more hospitals around the globe have engaged to offer the therapy despite there are important limitations for some regions for access. To obtain the best results, it is crucial to select the patients properly, do the implantation technique correctly, and follow-up the patients regularly. Even though there is an important momentum of SNM in pelvic floor disorders, there is no standardization on how to offer a proper SNM service. This article gives an overview of the main logistic fields to successfully set up a comprehensive and correct SNM provision.